Formation of lipofuscin-like autofluorescent granules in the retinal pigment epithelium requires lysosome dysfunction - Escrevente, Cristina (2021)
Funding Information: Supported by Funda??o para a Ciência e Tecnologia (FCT) ? Portugal co-funded by FEDER under the PT2020 Partnership Agreement (to MCS, including project PTDC/MED-PAT/30385/2017, iNOVA4Health-UIDB/04462/2020, research infrastructure PPBI-POCI-01-0145-FEDER-022122, M-ERA.NET 2/0005/2016), Boehringer Ingelheim (to MCS), Fight for Sight UK (to MCS), Wellcome Trust grant number 212216/Z/18/Z/ (to CEF). MJH was funded by Moor-fields Eye Charity with the Bill Brown 1989 Charitable Trust PhD studentship 538158, MLS was funded by FCT-CEECIND/01536/2018, ACF was funded by FCT PhD studentship (PD/BD/135503/2018). This work was developed with the support from the research infrastructure PPBI-POCI-01-0145-FEDER-022122, co-financed by FCT (Portugal) and Lisboa2020, under the PORTUGAL2020 agreement (European Regional Development Fund) and this article is supported by the LYSOCIL project funded by the European Union?s Horizon 2020 programme under grant agreement No. 811087. Funding Information: Supported by Fundação para a Ciência e Tecnologia (FCT) – Portugal co-funded by FEDER under the PT2020 Partnership Agreement (to MCS, including project PTDC/MED-PAT/30385/2017, iNOVA4Health-UIDB/04462/2020, research infrastructure PPBI-POCI-01-0145-FEDER-022122, M-ERA.NET 2/0005/2016), Boehringer Ingelheim (to MCS), Fight for Sight UK (to MCS), Wellcome Trust grant number 212216/Z/18/Z/ (to CEF). MJH was funded by Moor-fields Eye Charity with the Bill Brown 1989 Charitable Trust PhD studentship 538158, MLS was funded by FCT-CEECIND/01536/2018, ACF was funded by FCT PhD studentship (PD/BD/135503/2018). This work was developed with the support from the research infrastructure PPBI-POCI-01-0145-FEDER-022122, co-financed by FCT (Portugal) and Lisboa2020, under the PORTUGAL2020 agreement (European Regional Development Fund) and this article is supported by the LYSOCIL project funded by the European Union’s Horizon 2020 programme under grant agreement No. 811087. Publisher Copyright: Copyright 2021 The Authors